HEPATITIS-B AND ITS CURE: A STUDY ON THE AWARENESS LEVEL AMONG THE RURAL PEOPLE OF EASTERN UTTAR PRADESH - Nayak, Suresh Chandra; Lakhendra, Bala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Hepatitis B is the world’s most common liver infection. It is caused by the hepatitis B virus (HBV), which attacks and injures the liver. It is transmitted through blood, unprotected sex, shared or re-used needles, and from an infected mother to her newborn baby during pregnancy or delivery. It can cause scarring of the organ, liver failure, and cancer. However, a vaccine against hepatitis B has been available since 1982. The vaccine is 95% effective in preventing infection and the development of chronic disease and liver cancer due to hepatitis B. The hepatitis B virus can survive outside the body for at least 7 days. During this time, the virus can still cause infection if it enters the body of a person who is not protected by the vaccine. The incubation period of the hepatitis B virus is 75 days on average but can vary from 30 to 180 days. The virus may be detected within 30 to 60 days after infection and can persist and develop into chronic hepatitis B. The purpose of the present research paper is to study the awareness level of the rural people of eastern Uttar Pradesh and to analyze the effectiveness of the measures to cure Hepatitis B.